Using Authentic Material and Created Material (Teacher-Made) for English Language Teaching (ELT): Benefits and Limitations - Tira Nur Fitria (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
This research describes authentic materials and created materials (teacher-made materials) especially their benefits and limitations in English Language Teaching (ELT). This research is library research. The researcher collects data from books and articles published in journals related to authentic material and created material. The analysis shows considerations in English Language Teaching (ELT) are whether to use authentic or created material. Authentic materials refer to manuscripts, photos, videos, and other sources that are not prepared specifically for educational purposes. Meanwhile, created materials refer to textbooks or others specifically developed as teaching materials. In practice, two methods for teachers/lecturers use teaching materials such as adapting and adopting. Any course books or commercial textbooks can be utilized to be adapted as created materials. Authentic materials from a variety of sources that incorporate real language use also can be adopted. They also can use these two types of materials together in a language class to meet the requirements and interests of the students. But teachers/lecturers have to consider both authentic materials and created materials (teacher-made materials) related to the benefits and limitations. Teaching materials are very important for teachers and students in the learning process to improve the quality of learning. Without teaching materials, it will be difficult for teachers to increase the effectiveness of learning, and it will be difficult for students to follow the learning process in class.